Networking and anchoring through plectin: a key to IF functionality and mechanotransduction. (February 2015) - Wiche, Gerhard; Osmanagic-Myers, Selma; Castañón, Maria J
Abstract : Intermediate filaments (IFs) are involved in multiple cellular processes that are essential for the maintenance of cell and tissue integrity as well as response and adaption to stress. Mainly through pathological manifestations in patients and the analysis of genetic mouse models, it became evident that cytolinker proteins of the plakin protein family are essential for many of the functions ascribed to IFs. As discussed in this review, one of them, plectin, affects the assembly properties, interaction potential, compartmentalization, and linkage properties of IFs, making it to a key player for IF functionality. The far reaching consequences of IFs not being well-connected for skin and muscular integrity, migration, and mechanotransduction are highlighted.